2017
DOI: 10.3389/fncel.2017.00387
|View full text |Cite
|
Sign up to set email alerts
|

Netrin-1 Prevents Rat Primary Cortical Neurons from Apoptosis via the DCC/ERK Pathway

Abstract: In the nervous system, Netrin-1 serves as a neural guide, mediating the neuronal development. However, it remains blurred whether Netrin-1 can protect neurons from apoptosis induced by cerebral stroke. In the current study, the cultured rat primary cortical neurons were transfected with Netrin-1-encoding lentivirus before the oxygen-glucose-deprivation (OGD) treatment. Cell death and apoptosis were evaluated by lactate dehydrogenase (LDH) release and flow cytometry. We found that Netrin-1 attenuated OGD-induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…Here, we found that netrin-1 ameliorated UV-Binduced mitochondrial dysfunction and LDH release. Indeed, netrin-1 treatment has been shown to attenuate cell death and neuronal apoptosis in cultured primary cortical neurons after oxygen-glucose-deprivation (OGD) injury [24]. It should be noticed that UV-B exposure debilitated the features of ESCs through reducing the expression of integrin b1 and Krt19, two important ESC markers.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we found that netrin-1 ameliorated UV-Binduced mitochondrial dysfunction and LDH release. Indeed, netrin-1 treatment has been shown to attenuate cell death and neuronal apoptosis in cultured primary cortical neurons after oxygen-glucose-deprivation (OGD) injury [24]. It should be noticed that UV-B exposure debilitated the features of ESCs through reducing the expression of integrin b1 and Krt19, two important ESC markers.…”
Section: Discussionmentioning
confidence: 99%
“…For example, NT-1 interacted with DCC and activated the ERK pathway to promote the proliferation of endothelial cells and angiogenesis [ 31 ]. NT-1 combined with DCC to reduce the DNA damage and apoptosis in cultured primary neurons [ 32 ]. UNC5H2 was the receptor responsible for protecting BBB breakdown [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, in some postmitotic cells, such as neurons, IGF‐1 protects them from apoptosis by upregulating the antiapoptotic protein Bcl‐2 and decreasing caspase‐3 activity . In addition, netrin‐1 protects cortical neurons from apoptosis by activating the ERK signaling pathway . In this context, we suggest that in response to certain cell damage, insulin/IGF‐1 inhibits apoptosis to control tissue destruction and contributes to cell survival, proliferation, damage repair, and regeneration.…”
Section: Mechanisms Of Apoptosis Dysregulation In Agingmentioning
confidence: 93%